2020
DOI: 10.21203/rs.3.rs-18870/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scleroderma-specific autoantibodies embedded in immune complexes mediate endothelial damage: an early event in the pathogenesis of systemic sclerosis

Abstract: Background: Consistently with their diagnostic and prognostic value, autoantibodies specific for systemic sclerosis (SSc) embedded in immune complexes (ICs) elicited a pro-inflammatory and pro-fibrotic cascade in healthy skin fibroblasts, engaging Toll-like Receptors (TLRs) via their nucleic acid components. The objective of this study was to investigate the pathogenicity of SSc-ICs in endothelial cells.Methods: ICs were purified from sera of SSc patients bearing different autoantibody specificities (antibodie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…On the other way, the other study suggested that innate TLR2 signals convert transient T helper 2 cell-mediated dermatitis into persistent inflammation, as seen in chronic atopic dermatitis, through IL-4-mediated suppression of IL-10 35 . TLR9 is well known as a receptor that responds to nucleic acids, and there have been several reports that showed association with skin lesions of autoimmune diseases 36,37 . A recent study suggested that systemic sclerosis immune complexes have the potential pathogenicity mediated by TLR9 via the interaction with nucleic acid fragments on fibroblasts 38 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other way, the other study suggested that innate TLR2 signals convert transient T helper 2 cell-mediated dermatitis into persistent inflammation, as seen in chronic atopic dermatitis, through IL-4-mediated suppression of IL-10 35 . TLR9 is well known as a receptor that responds to nucleic acids, and there have been several reports that showed association with skin lesions of autoimmune diseases 36,37 . A recent study suggested that systemic sclerosis immune complexes have the potential pathogenicity mediated by TLR9 via the interaction with nucleic acid fragments on fibroblasts 38 .…”
Section: Discussionmentioning
confidence: 99%
“…, 40,46,47]. ANA-IC have been shown to modulate pro-inflammatory and pro-fibrotic pathways in healthy control fibroblasts and endothelial cells thought to be mediated via toll-like receptors [46].…”
Section: Molecular Basis Of Pathogenic Mechanisms Of Antinuclear Auto...mentioning
confidence: 99%
“…ANA-IC have been shown to modulate pro-inflammatory and pro-fibrotic pathways in healthy control fibroblasts and endothelial cells thought to be mediated via toll-like receptors [46]. Distinct differences in between ANA-IC subset and gene expression with ATA-ICs influencing Interferon mRNA signatures whilst ARA-IC activating nuclear factor-kB (NFkB) signaling [46]. ATA positive SSc (6.5 OR) [46] ACA, anticentromere antibodies; ARA, anti-RNA polymerase III; ATA, antitopisomerase I; HLA, human leukocyte antigens; OR, odds risk; SSc, scleroderma.…”
Section: Molecular Basis Of Pathogenic Mechanisms Of Antinuclear Auto...mentioning
confidence: 99%
See 2 more Smart Citations